Influence of Performance and Discipline on Work Productivity Among Employees of PT Pelabuhan Indonesia (Persero) Regional 2 Cirebon - Trisno Haji; Ade Setiadi; Susi Sugiyarsih (Universitas Wiralodra, 2025)
This study examines the influence of employee performance and work discipline on work productivity at PT. Pelabuhan Indonesia (Persero) Regional 2 Cirebon. The background of this research arises from the observed decline in productivity among employees, despite existing performance management and disciplinary frameworks within the organization. The study aims to determine both the partial and simultaneous effects of performance and discipline on productivity, providing empirical evidence to support managerial policy and human resource development within public enterprises. A quantitative approach was employed using a survey method. Data were collected through questionnaires distributed to 60 employees, selected randomly from a population of 150. Statistical analysis was performed using multiple linear regression. The findings indicate that employee performance and work discipline each have a positive and significant effect on work productivity. Moreover, when tested simultaneously, both variables jointly explain 57.8% of the variation in productivity levels. The study reveals that discipline plays a more dominant role than performance in determining productivity outcomes. This research underscores the importance of integrating performance management with strict adherence to work discipline. It recommends continuous monitoring, employee engagement, and reinforcement of organizational behavior to ensure sustained productivity in public sector institutions.